Features of the formation of regional policy of Ukraine during transformational changes - Сімків, Л. Є. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The theoretical principles of regional policy associated with structural realignment regions and regional socio-economic development area is analysed. Priority approaches to the formulation and implementation of state regional policy of Ukraine proceeding from the basic long-term objectives: socio-economic growth of the regions overcoming major interregional disparities, achieving acceptable norms and standards and living conditions of the people, were determinated. Justifiably, that the management of socio-economic development of the region in modern conditions must come with the necessary close cooperation between national, regional and local authorities in the development and implementation of regional policy, defining strategic goals; make up a proper legal-adeptly, which should determine the ratio of the specific weight of State-Government and regional social impacts; contribute to the implementation of economic reforms, creation of conditions for the real impact of territorial communities and the population of the regions on the processes of implementation of regional policy; promote the observance of the principle of equality of all subjects of the State in relations between themselves and with the bodies of public administration concerning solving life and comprehensive development of the territories; maintain and strengthen the integrity and unity of the society and the State.